Forming of the structure of surface volume of the cast macrogeterogeneous composition materials in conditions of low speed friction without lubricant - V. Ja. Kezik; A. S. Kalinichenko; R. K. Ivanova (Литьë и металлургия)
There are investigated the specific features transformation in the composite materials of macro- heterogeneous structure during dry friction. There are shown some common peculiarities of the structure formation during high and low speed dry friction without any lubricant.